2016
DOI: 10.11138/mltj/2016.6.3.402
|View full text |Cite
|
Sign up to set email alerts
|

Complications in Hip Arthroscopy

Abstract: SummaryBackground: Recent developments in hip arthroscopic techniques and technology have made it possible in many cases to avoid open surgical dislocation for treating a variety of pathology in the hip. Although early reports suggest favourable results' using hip arthroscopy and it has been shown to be a relatively safe procedure, complications do exist and can sometimes lead to significant morbidity. Methods: This is a review article. The aim of this manuscript is to present the most frequent and/or serious … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 85 publications
1
10
0
Order By: Relevance
“… 5 , 8 , 10 Although this was not evidenced in our study, this finding is similar to that reported by Haskins et al 7 Several studies have recommended the close monitoring of fluid balance and the use of pump pressures between 40 and 50 mm Hg to reduce the risk of extravasation. 12 , 13 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 5 , 8 , 10 Although this was not evidenced in our study, this finding is similar to that reported by Haskins et al 7 Several studies have recommended the close monitoring of fluid balance and the use of pump pressures between 40 and 50 mm Hg to reduce the risk of extravasation. 12 , 13 …”
Section: Discussionmentioning
confidence: 99%
“… 17 The most common complications are traction-related injuries, chondrolabral damage, deep vein thrombosis, pulmonary embolism, and fluid extravasation. 2 , 12 , 17 …”
mentioning
confidence: 99%
“…It has been hypothesized that suture material may contribute to the development of post-operative capsulolabral adhesion [15, 23]. Capsulolabral adhesions are often seen in revision hip arthroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…This can lead to the development of scar tissue during labral surgery. The presence of suture material has been shown to cause an inflammatory response in rabbit models, and therefore, may contribute to the formation of scar tissue [15, 23].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from patient factors, it is unknown if hip arthroscopy carries increased risk for the development of VTE compared to knee arthroscopy where routine anti-VTE chemoprophylaxis is not recommended. An arthroscopic hip procedure includes foot and ankle immobilization, use of traction, surgical manoeuvres performed in proximity to the deep femoral vein system where thrombi can form and usually spinal or epidural anaesthesia which causes venodilation and blood stasis [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%